Review of Gini Ratio on Economic Growth with Human Mobility Mediation during Indonesia's Covid-19 Era - Siregar, Sri Indriyani; Al Rasyid, Firda Agil (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
The COVID-19 pandemic has changed people's lives a lot; even the realization of the National Mid-Term Development Plan (RPJMN) has been disrupted. The changes in population mobility patterns have intervened in the efforts to reduce regional inequality to increase economic growth. This study aims to gain new insight into the provincial classification of the Gini ratio and the relationship between economic growth and the Gini ratio, as well as human mobility. In addition, this aims to know whether mobility is proven to mediate the Gini ratio and economic growth relationship using Path Analysis using Robust Regression. As for the data source, this study uses the provincial panel data from the 1st Semester of 2020 to the 2nd Semester of 2021 from Statistics Indonesia and Google Community Mobile Reports. This study shows that the Gini ratio has changed many provinces to a lower classification, indicating that the pandemic affects the upper-middle-class economy. Furthermore, it can be significantly proven that human mobility affects the relationship between income inequality and economic growth (Sobel test p-value = 0.0207). This study can be used as an evaluation material for the government and the stakeholders. Especially to formulate strategies so that the increase of human mobility has an economic goal and in a fit human body condition to restore the economic wheels and not become a time bomb for the COVID-19 transmission in Indonesia.